BLEEDING STATUS, HANDLING TIME AND INITIAL MORTALITY OF RECREATIONAL FISHERIES IN CHUB (SQUALIUS CEPHALUS) (LINNAEUS 1758) - Atessahin, Tuncay (Parlar Scientific Publications (P S P), 2019)
The aim of this study is to determine the bleeding status, handling time, and initial mortality caused by the anatomical status of fish hooks in a fish's oral mouth. Observations were conducted during the course of a total of 30 amateur recreational fishing expeditions to catch Squalius cephalus between July, 2013, and December, 2015. Anatomical conditions of the hooks as lodged in a fish's jaws (lower, upper, external, upper and lower jaws), hook removal times, and overall length of the captured fish were compared on the basis of the type of lure and hook used (i.e., spinner, spoon). Only four (of the 111 fish caught in total) were observed to have died within one hour of capture. All of these deaths occurred in fish caught by spinner. It was observed that the bleeding rates proportionally increased with the increase in the amount of time required to remove the hook. The difference between the anatomical status and the time of removal from the hook was statistically found to be significant (ANOVA, F = 8.842 p <0.01). In the fish that were hooked on both jaws, the time to remove the hook was longer. Therefore, bleeding (and mortality) was more prevalent in these fish. To create more sustainable recreational fisheries, it can be concluded that the awareness of fishermen (and state authorities) should be focused on greater selectivity in the types of hooks that are used; fish hooks that cause less damage to the fish lead to an increase in overall fish welfare, and ultimately facilitate a more sustainable fishing industry.
Keywords: Catch and Release; Mortality Rate; Squalius cephalus; Spinner; Spoon